A multi-scale analysis method for the simulation of tunnel excavation in sandy cobble stratum. (January 2019) - Du, Xiuli; Zhang, Pei; Jin, Liu; Lu, Dechun
Highlights: A multi-scale method for modeling tunnel excavation in sand gravel strata is proposed. A homogenization method for determining the mechanical properties of SRM is developed. The multi-scale simulation method has a high efficiency without loosening accuracy. Abstract: Sandy cobble stratum is a kind of heterogeneous geological body. A further study on the safety of wall rocks and underground structure demands developing suitable analysis method to simulate tunnel excavation in such a formation. Macro-scale simulations assume the sandy cobble soil to be homogeneous in numerical models. They get more efficient computing, but have difficulties in capturing enough information about the meso-scopic fields needed. Meso-scale simulations explicitly represent the individual components of the heterogeneous internal material structure in numerical models, e.g. the shape and the spatial distribution of rocks. They achieve high accuracy, but large computational cost would be needed. To reduce the numerical effort with the precision guaranteed, a multi-scale analysis method for simulating tunnel excavation in sandy cobble strata is proposed. In this method, the numerical model is divided into two regions, involving the meso-scale region and macro-scale region. The meso-scale region is a critical sub-domain disturbed by tunnel excavation, in it, the rocks and soil are considered as separate constituents. In the macro domain, the sand gravel soil was regarded as homogeneous materials whose effective material parameters were determined using an equivalent homogenization method. Three critical issues in the multi-scale method are explored, including: (i) the determination of meso domain and macro domain, (ii) the determination of rock maximum size that can be homogenized in the meso domain and iii) the determination of effective material parameters of soil-rock mixture during the equivalent process. By comparing with simulation results predicted by macro-scale and meso-scale simulation methods, the validation of the proposed multi-scale simulation method was carried out. The result indicates that the proposed multi-scale analysis method has a high efficiency without loosening accuracy on the simulation of tunnel excavation in sandy cobble stratum.